Being Independent is a Great Thing: Subjective Evaluations of Self-Employment and Hierarchy - Bruno Frey; Matthias Benz (Center for Economic Studies and ifo Institute (CESifo), 2003)
One can be independent, or subject to decisions made by others. This paper empirically tests whether individuals attach an intrinsic value to the institutional difference between independence and hierarchy. Taking self-employment as an important case of independence, it is shown that the self-employed derive more utility from their work than people employed by an organization, irrespective of income gained or hours worked. This is evidence for procedural utility: people do not only value outcomes, but also the conditions and processes leading to these outcomes.
Keywords: 330; procedural utility; institutions; hierarchiy; self-employment; job satisfaction